1980
DOI: 10.2105/ajph.70.12.1297
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in spontaneous abortions.

Abstract: Using a national sample of hospital discharges, we found identical seasonal patterns for spontaneous abortions and conceptions but no significant seasonal variation in the rate of spontaneous abortions per 1,000 conceptions. The differences between our findings and those of previous investigators of spontaneous abortion may reflect our more comprehensive definition of spontaneous abortion, our more complete estimate of the monthly number of conceptions, and our more rigorous statistical analysis. The periodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
1

Year Published

1986
1986
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 1 publication
(1 reference statement)
0
16
1
Order By: Relevance
“…Kaplan (1973) found a significant excess of spontaneous abortions during March through June. Warren et al (1980) found a significant seasonal pattern for the number of spontaneous abortions (above average from January through March and July and August), but the monthly rate of spontaneous abortions was not significant. In this study, we found no seasonal pattern for either the number or the rate of spontaneous abortions.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Kaplan (1973) found a significant excess of spontaneous abortions during March through June. Warren et al (1980) found a significant seasonal pattern for the number of spontaneous abortions (above average from January through March and July and August), but the monthly rate of spontaneous abortions was not significant. In this study, we found no seasonal pattern for either the number or the rate of spontaneous abortions.…”
Section: Discussionmentioning
confidence: 72%
“…Kaplan (1973) and McDonald (1971) found an excess of spontaneous abortions in the spring (after controlling for conceptions) and suggested that infective agents that are epidemic in the spring may be the explanation. In contrast, Warren et al (1980) found no monthly excess of spontaneous abortions after controlling for conceptions. He and his colleagues concluded that the monthly number of spontaneous abortions is probably related to the seasonal pattern of conceptions.…”
mentioning
confidence: 80%
See 3 more Smart Citations